The giraffe kidney tolerates high arterial blood pressure by high renal interstitial pressure and low glomerular filtration rate. (15th June 2015) - Damkjær, M.; Wang, T.; Brøndum, E.; Østergaard, K. H.; Baandrup, U.; Hørlyck, A.; Hasenkam, J. M.; Smerup, M.; Funder, J.; Marcussen, N.; Danielsen, C. C.; Bertelsen, M. F.; et al.
Abstract Background The tallest animal on earth, the giraffe (Giraffa camelopardalis) is endowed with a mean arterial blood pressure (MAP) twice that of other mammals. The kidneys reside at heart level and show no sign of hypertension‐related damage. We hypothesized that a species‐specific evolutionary adaption in the giraffe kidney allows normal for size renal haemodynamics and glomerular filtration rate (GFR) despite a MAP double that of other mammals. Methods Fourteen anaesthetized giraffes were instrumented with vascular and bladder catheters to measure glomerular filtration rate (GFR) and effective renal plasma flow (ERPF). Renal interstitial hydrostatic pressure (RIHP) was assessed by inserting a needle into the medullary parenchyma. Doppler ultrasound measurements provided renal artery resistive index (RI). Hormone concentrations as well as biomechanical, structural and histological characteristics of vascular and renal tissues were determined. Results GFR averaged 342 ± 99 mL min−1 and ERPF 1252 ± 305 mL min−1. RIHP varied between 45 and 140 mmHg. Renal pelvic pressure was 39 ± 2 mmHg and renal venous pressure 32 ± 4 mmHg. A valve‐like structure at the junction of the renal and vena cava generated a pressure drop of 12 ± 2 mmHg. RI was 0.27. The renal capsule was durable with a calculated burst pressure of 600 mmHg. Plasma renin and AngII were 2.6 ± 0.5 mIU L−1 and 9.1 ± 1.5 pg mL−1 respectively. Conclusion In giraffes, GFR, ERPF and RI appear much lower than expected based on body mass. A strong renal capsule supports a RIHP, which is >10‐fold that of other mammals effectively reducing the net filtration pressure and protecting against the high MAP.